2017
DOI: 10.1515/stuf-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Polar questions, social actions and epistemic stance

Abstract: This article describes the relationships between epistemic stance, social actions and form variants of polar questions in Estonian institutional information-seeking dialogues and compares the results with ordinary conversation in English, Dutch, and Danish. Estonian and English use a polarized system where the unknowing stance is formulated by particles and/or inversion, and knowing stance by declaratives and sentence-final markers. Dutch and Danish use an asymmetrical system where unknowing stance uses an inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We did not analyse interrogative sentences with other functions: directives, rhetorical questions, other-initiations of repair, etc. (see, e.g., Hennoste, Rääbis & Laanesoo 2017). Due to the limited number of interrogative clauses in the corpora, our analyses will be qualitative.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not analyse interrogative sentences with other functions: directives, rhetorical questions, other-initiations of repair, etc. (see, e.g., Hennoste, Rääbis & Laanesoo 2017). Due to the limited number of interrogative clauses in the corpora, our analyses will be qualitative.…”
Section: Methodsmentioning
confidence: 99%
“…Still, the role of intonation in forming polar questions in Livonian needs further study to say anything decisive. By comparison, a study on Estonian revealed that spoken language intonation may support interpreting an utterance as a question but not necessarily (Hennoste, Rääbis & Laanesoo 2017; see also Section 2).…”
Section: Other Ways Of Forming Polar Questionsmentioning
confidence: 99%
“…could be interpreted as a straight-forward request to know what the listener is looking at, but also as a directive for the listener to stop looking at the speaker, depending on the context and intonation of said question. The same principle is true in Estonian, where questions (including mis-initial questions) can function in a variety of ways and oftentimes fill more than one pragmatic function in a conversation (seeHennoste, Rääbis & Laanesoo 2017, Laanesoo 2018, Rumm 2019.…”
mentioning
confidence: 92%